Effect of Gibberellin, Ascorbic acid and Salicylic acid on Seed Quality, Photosynthesis Pigments and Malondialdehyde Content of Seedling From Sunflower Deteriorated Seeds - Ameneh Akbarzadeh Sharafi; Hamid Reza Eisvand; N. Akbari; D. Goodarzi (علوم و فناوری بذر ایران)
In order to study effects of seed priming with Gibberellin (GA), Ascorbic acid (AsA) and Salicylic acid (SA) on mitigation of seed deterioration damage and improvement of seed and seedling qualities of three sunflower cultivars (Farrokh, Barzegar and Shamshiri), a pot experiment was done in 2016. This research was carried out as a factorial experiment based on RCBD with three replications. Seeds were exposed to accelerated aging then primed. Priming treatments were included: control, hydropriming, GA (50 and 75 ppm), AsA (100 and 150 ppm), SA (138 and 207 ppm), GA 50 ppm + AsA 100ppm, GA50 ppm + SA 138 ppm, AsA 100ppm + SA 138ppm, and GA 50ppm + AsA 100ppm + SA 138 ppm. Barzegar cultivar had better seedling emergence percentage and rate than the Shamshiri and Farrokh. Seedling emergence was improved by priming treatments; however, suitable treatments were different for the cultivars. Maximum seedling emergence percentage was obtained in Barzegar by GA 50ppm + SA 138ppm; however in Shamshiri and Farrokh by hydropriming. Priming improved seedling emergence rate of the three cultivars, but the response to priming was cultivar specific. Priming decreased seedling malondialdehyde (MDA) significantly in three cultivars. The lowest MDA content was obtained in Barzegar cultivar primed by AsA + SA.